2019
DOI: 10.1038/s41598-019-40705-4
|View full text |Cite
|
Sign up to set email alerts
|

Observation of magnetic skyrmions in unpatterned symmetric multilayers at room temperature and zero magnetic field

Abstract: Magnetic skyrmions are promising candidates for the next generation of spintronic devices due to their small size and topologically protected structure. One challenge for using these magnetic states in applications lies on controlling the nucleation process and stabilization that usually requires an external force. Here, we report on the evidence of skyrmions in unpatterned symmetric Pd/Co/Pd multilayers at room temperature without prior application of neither electric current nor magnetic field. Decreasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 43 publications
3
51
0
Order By: Relevance
“…Figures 5(a) showing skyrmions in magnetic materials with uniaxial magnetic anisotropy. [31][32][33] Each "worm" (band domain) and each spherical domain correspond to one Hall-effect quantum, and the formation of these domains is likely to involve branching from the middle of the relatively thick ribbons. 34 An excessive applied field leads to the disappearance of skyrmions in NiMnGa, and a nearly uniform magnetization distribution results, Fig.…”
mentioning
confidence: 99%
“…Figures 5(a) showing skyrmions in magnetic materials with uniaxial magnetic anisotropy. [31][32][33] Each "worm" (band domain) and each spherical domain correspond to one Hall-effect quantum, and the formation of these domains is likely to involve branching from the middle of the relatively thick ribbons. 34 An excessive applied field leads to the disappearance of skyrmions in NiMnGa, and a nearly uniform magnetization distribution results, Fig.…”
mentioning
confidence: 99%
“…We know that the challenge for using magnetic skyrmions in applications is to find room temperature-stabled skyrmions without external force. Recently, several experiments have demonstrated that ultrathin ferromagnetic/heavy metal multilayers are good structures that can host skyrmions at zero magnetic field and room temperature 42 44 , and its size and density also can be controlled by the shape and size of the nanostructure 44 . Our above results show an evidence that curvature is also a method to reduce the magnetic field to stabilize skyrmions.…”
Section: Resultsmentioning
confidence: 99%
“…If all multiple intersections of each set curve occur at one quarter, but the central part has single intersections, we obtain double loops as inFigure 4. This result takes place at low temperatures (T ≤ 300[K]), see also[31].…”
mentioning
confidence: 79%